COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF ORTHOPEDIC TREATMENT OF PARTIAL DENTITION DEFECTS USING DIGITAL TECHNOLOGIES - Mukhtasar A. Anvarova; Alisher A. Akhmedov (Central Asian Journal of Medicine, 2024)
In a number of studies, electronic axiography and digital kinesiography were used to determine the effectiveness of various orthopedic manipulations before and after treatment V. D. et al., 2014; Persin L. S. et al., 2019; Arutyunov S. D. et al., 2019; Mammadov A. A. et al., 2019; Dubova L. V. et al., 2020; Lebedenko I. Y. et al., 2022]. Individualized methods of using digital and traditional technologies have not been developed in assessing the effectiveness of orthopedic planning and treatment of partially toothless patients, which is the most important direction of their use in clinical practice. The most important of them include evaluating the effectiveness of orthopedic treatment, evaluating the occlusive ratio and the level of its correction, evaluating the effect of established orthopedic coatings on chewing muscles and oral microbiocenosis, determining indications for orthopedic treatment of patients with partial tooth loss. and planning tactics.